2022
DOI: 10.3390/ijms23126595
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Coordination Compounds with Benzimidazole Derivatives: Synthesis, Structure, Antimicrobial Activity and Potential Anticancer Application

Abstract: Developing new, smart drugs with the anticancer activity is crucial, especially for cancers, which cause the highest mortality in humans. In this paper we describe a series of coordination compounds with the element of health, zinc, and bioactive ligands, benzimidazole derivatives. By way of synthesis we have obtained four compounds named C1, C2, C4 and C4. Analytical analyses (elemental analysis (EA), flame atomic absorption spectrometry (FAAS)), spectroscopic (Fourier transform infrared spectroscopy (FT-IR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 86 publications
2
6
0
Order By: Relevance
“…At the present time, there are very many studies of the substituted benzimidazole derivatives, which showed a distinctive activity to kill microbes or stop their growth, and that many of the prepared derivatives were efficacy comparable or superior to the standard drugs used for the same purpose [138]- [147] . [148]- [153] 4.7.…”
Section: Manuscriptmentioning
confidence: 99%
“…At the present time, there are very many studies of the substituted benzimidazole derivatives, which showed a distinctive activity to kill microbes or stop their growth, and that many of the prepared derivatives were efficacy comparable or superior to the standard drugs used for the same purpose [138]- [147] . [148]- [153] 4.7.…”
Section: Manuscriptmentioning
confidence: 99%
“…It was based on the PASS Online approach [ 13 , 14 , 15 ] and the experimental data from ChEMBL’s 23 databases for 59,882 compounds. Since then, more than 80 papers have been published with studies using CLC-Pred to evaluate the cytotoxicity of new chemical compounds [ 16 , 17 ], natural compounds [ 18 , 19 , 20 ], as well as in studies aimed at finding new antitumor substances [ 21 , 22 ]. In the present paper, we offer a new version of the web application, CLC-Pred 2.0, that is based on significantly bigger data on the cytotoxicity of compounds in relation to cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Minerals are unquestionably essential for plants to develop effectively [ 20 ]. The use of benzimidazole as a ligand for transition metal ions with a variety of biological molecules, including ion heme systems, vitamin B 12, and its derivatives, and various metal lipoproteins is very common [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of benzimidazole as a ligand for transition metal ions with a variety of biological molecules, including ion heme systems, vitamin B 12, and its derivatives, and various metal lipoproteins is very common [ 21 ]. Furthermore, the complexes of metal salts with benzimidazole derivatives have been extensively investigated as a model structure of numerous key biological molecules [ 20 ]. It has been reported previously that, occasionally, biologically relevant ligands are more active in metal complexes than in the free form [ 22 ].…”
Section: Introductionmentioning
confidence: 99%